Understanding arithmetic - Swain, Robert L. (Robert Lomond); Nichols, Eugene Douglas, 1923- (New York : Holt, Rinehart and Winston, 1965)
Explains basic mathematics from number systems and operations through coordinate geometry. Useful for a general overview of elementary school mathematics
Keywords: Number concept; Arithmetic -- Foundations; Arithmetic -- Study and teaching; Mathematics; Coordinates